AN ANALYSIS OF STUDENTS’ ABILITY IN PUBLIC SPEAKING AT UNIVERSITAS PGRI PALEMBANG - Ayu Meilani; MA Barokatul Qodiri Sidomulyo; Sri Hartati (Jurnal Didascein Bahasa, 2018)
The objective of this study was to know factors thataffect the emergence of fear of public speaking of students’ English education at Universitas PGRI Palembang in terms of experiencing panic and dread, fearing at the fear itself, and negative beliefs about themselves and the audience.The method of this study was descriptive qualitative analysis.The participants of this study were 40 students of English Education at Universitas PGRI Palembang in the Academic Years of 2017/2018. The data were analyzed by checking the respond of the questionnaire and calculating the percentage analysis. Results of the study showed that those factors were experiencing panic and dread in categories feeling shame and feeling being alone, and then perceives something to be a significant danger or threat;fearing at the fear itself in categories pounding heart, trembling/shaking, lightheaded, numbness, and fear of losing control; andnegative beliefs about themselves and the audience in categories negative beliefs about themselves and the audience. Keywords: students’ ability, and public speaking.